Overwinter sea-ice characteristics important for Antarctic krill recruitment in the southwest Atlantic. (October 2021) - Veytia, Devi; Bestley, Sophie; Kawaguchi, So; Meiners, Klaus M.; Murphy, Eugene J.; Fraser, Alexander D.; Kusahara, Kazuya; Kimura, Noriaki; Corney, Stuart
Highlights: Regional indices of Antarctic krill recruitment developed for southwest Atlantic over 35 years. Mechanistically informed indicators of sea-ice habitat estimated from model output. Correlation between sea ice indicators and recruitment highlight plausible habitat. New indicators improve understanding of impacts of changing sea ice. Abstract: Climate change alters the extent and structure of sea-ice environments, which affects how they function as a habitat for polar species. Identifying sea-ice characteristics that serve as indicators of habitat quality will be crucial to the monitoring and management of climate change impacts. In the Southern Ocean, Antarctic krill is a key prey species and fishery target. Krill larvae depend upon sea-ice habitats to survive the winter and recruit to the population in spring. Existing observations of sea-ice characteristics lack sufficient spatiotemporal coverage to quantify which ones contribute to favourable overwintering habitat, leading to uncertainties in how current and future changes in sea ice affect krill populations. Here, we derive regional-scale indices of annual krill recruitment spanning 35 years across the southwest Atlantic. To develop meaningful indicators of sea-ice habitat, we selected variables from a high-resolution sea-ice model that are hypothesized as relevant for larval habitat use. The resulting correlations between recruitment and sea-ice indicators vary by region and show remote connections to sea ice that correspond with established theories of larval transport. Through an improved representation of sea-ice habitat quality, as compared with using more traditional satellite-derived variables such as sea-ice extent and duration, we highlight plausible regions of overwintering habitat. Our findings improve current understanding of how krill are likely responding to changing sea ice and support emerging views that larval habitat use is complex. Furthermore, regional variation in larval dependence on sea ice may provide pockets of resilience to change for the broader krill population.